WARIA DAN SHALAT REINTERPRETASI FIKIH UNTUk KAUM WARIA - Masnun, Masnun (Sunan Kalijaga State Islamic University & The Asia Foundation, 2011)
To live as a minority in a mainstream culture is far for easy, especially for a group viewed with such novelty and queerness by the society, like the transgender. Nevertheless, the transgender seem to be holding steady in the face of a barrage of negative assumptions and discrimination. Much of those came from the interpretations of certain religious entities, and imposing upon them massive social, spiritual and psychological burdens. The impression from such discrimination is that the transgender are rejected both in this world and the hereafter. One such problem has to do with the shalat, where they stand on unclear grounds upon the position in the lines of prayer and the defining of the limits of their aurat. This article thus tries to prove that Islam serves and accommodates all entities not excluding those of the transgender.